Sustainable conversion of textile industry cotton waste into P-dopped biochar for removal of dyes from textile effluent and valorisation of spent biochar into soil conditioner towards circular economy. (1st November 2022) - Kar, Susmita; Santra, Bhaskar; Kumar, Sunil; Ghosh, Sourja; Majumdar, Swachchha
Abstract: Effective immobilization of industrial waste into biochar development could be one of the most promising technologies for solid waste management to achieve circular economy. In this study, post-industrial cotton textile waste (PICTW), a cellulose rich industrial waste, was subjected to slow pyrolysis to develop a surface engineered biochar through phosphoric acid impregnation. Biochar produced at 500 °C designated as PICTWB500 showed a maximum methylene blue number (240 mg g −1 ) with remarkable specific surface area of 1498 m 2  g −1 . FESEM, FTIR, XRD and Raman spectra analysis were performed to investigate the surface texture and functionalities developed in the biochar. Adsorption efficiency of the biochar was assessed using drimarene red, blue, violet, and black dyes as model dye pollutants in batch mode at different biochar dose, pH and contact time. The maximum monolayer adsorption capacity was obtained in the range 285–325 mg g −1 for different dyes, determined from Langmuir adsorption model. The kinetic behaviour was more favourable with the pseudo second-order model. The recycling ability of PICTWB500 was proven to be effective up to 6th cycle without compromising its adsorption efficiency significantly. This study demonstrated an excellent adsorption capability of the biochar in dye laden real textile effluent and recycling of spent biochar as a precursor of bio compost. Hence, this study established a dual win strategy for waste utilization in textile industry using a closed loop approach with substantial techno-economic feasibility that may have potential applications. Graphical abstract: Image 1 Highlights: Cotton Textile waste was successfully converted into surface engineered biochar. 500 °C was the optimal pyrolysis temperature for biochar with highest surface area. Maximum monolayer adsorption capacity was 285–325 mg g −1 for reactive model dyes. Real textile effluents were used to analyse the efficiency of the biochar. Spent biochar derived compost could be used as soil conditioner for plant growth.